Hospital Wastewater as a Reservoir for Antibiotic Resistance Genes: A Meta-Analysis - Zhang, Shengcen; Huang, Jiangqing; Zhao, Zhichang; Cao, Yingping; Li, Bin (Frontiers in Public Health, 2020)
Background: The emergence and dissemination of antibiotic resistance genes (ARGs) in the environment poses a huge global health hazard. Hospital wastewater (HWW), in which a high density of antibiotic residues and antibiotic-resistant bacteria are present, may be a reservoir of ARGs dissemination into the environment. Our meta-analysis comprehensively analyzes the prevalence of ARGs in HWW, as well as the influencing factors in ARGs distribution. Methods: Online databases were used to search for literature using the subject terms: "Drug Resistance" AND "Genes" AND "Hospitals" AND "Wastewater". Two reviewers independently applied predefined criteria to assess the literature and extract data including "relative abundance of ARGs", "title", "authors", "country", "location", "sampling year" and "sampling seasons". The median values and 95% confidence intervals of ARGs abundance were calculated by Wilcox.test function in R. Temporal trends, spatial differences, seasonal variations and removal efficiency of ARGs were analyzed by Pearson correlation analysis and Kruskal-Wallis H test. Results: Resistance genes to carbapenems, sulfonamides, tetracyclines and mobile genetic elements were found at high relative abundance (>10-4 gene copies/16S rRNA gene copies) in HWW. The abundance of resistance genes to extended-spectrum β-lactams, carbapenems, sulfonamides and glycopeptide significantly decreased, while tetracycline resistance genes abundance increased from 2014 to 2018. The abundance of ARGs was significantly different by country but not by season. ARGs could not be completely removed by on-site HWW treatments and the removal efficiency varies for different ARGs. Conclusions: HWW presents more types of ARGs, and their abundance is higher than those in most wastewater systems. HWW may be a reservoir of ARGs and play an important role in the dissemination of ARGs.